Identifying, assessing and treating complicated post-traumatic stress disorder in adolescence: a single-case quasi-experimental design with clinical case report. (3rd March 2017) - Cowles, Megan; Davis, Jennifer
Abstract: The far-reaching impact of post-traumatic stress disorder (PTSD) on a person's life is well documented, yet PTSD often goes undetected and untreated. Previous literature suggests that there may be particular challenges in assessing PTSD in children and adolescents. There is evidence that once PTSD has been identified, a trauma-focused cognitive behavioural therapy (TF-CBT) approach is effective at treating PTSD in young people. Where PTSD in adolescents presents in response to multiple traumas it may be necessary to make some modifications to treatment protocols. This might include offering more sessions, extending the stabilization period, addressing common trauma themes, and tackling additional issues that may arise beyond a simple PTSD presentation. This single-case quasi-experimental design ( n = 1 ) details the assessment (phase A) and treatment with individualized TF-CBT (phase B) of previously undiagnosed PTSD in response to multiple events in an adolescent girl who had been seen by several mental health professionals previously. The paper is also a clinical case report, paying particular attention to how PTSD was assessed and what other factors, for example emotion regulation, self-esteem and relationships, were found to be important. Trauma, anxiety and depression were measured with the Child PTSD Symptom Scale and the Revised Children's Anxiety and Depression Scale. Scores reduced from clinically significant to non-clinical levels by the end of treatment, with these gains being maintained at 3-month follow-up. Suggestions are made around assessing and treating trauma responses in young people, especially where PTSD exists in response to multiple traumas.